The face of social museology in museums and museum processes in Amazon (Cadernos de Sociomuseologia, 2022)
The Face of Social Museology in Museums and on the Amazonian Museal Process is result of this Doctorate research in Sociomuseology at the Lusophone University of Humanities and Technologies of Lisbon City in Portugal carried out from 2009 to 2019. The thesis theme is part of the Museology and Local Heritage research line. The research's objective is a broad discussion on the democratization process of museums in Pará's Amazon, with Social Museology as an analysis instrument of decolonization and cultural resistance of modern communities which are subordinated to the remains of coloniality's power, of being and having in Latin America.The research is an outcome of a 10 years work (2008 to 2018) in three museums and a museum process in the State of Pará in Northern Brazil. The research is based on Social Museology as a field of knowledge committed to the “use of memories' power, heritage and museums in favor of popular communities, indigenous peoples, quilombolas and social movements” (Chagas & Gouveia, 2014, p.16). The methodology is documentary, ethnographic, procedural and cartographic. The research is result not only of interviews collected in Pará's municipalities, but also through meetings,social networks conversations, museological experiences with the involvement of cultural managers, museum participants, cultural activists, non-visiting audiences of museums that through these processes contributed to this text construction.The research analysis made it possible to design a multiple face of the Amazonian museologies, where memories are living beings because:point to Museology as an instrument to face problems and changes in society, expand the museum's vision beyond the categories established by the International Museum Committee and the Brazilian Institute of Museums,identify a diverse museal culture in the Amazon that presents its way of being, power and having and finally,signals the museums' responsibility as political agents of memory, being this questioner, denouncer, articulator, mobilizer, promoter and mediator of heritage references. Keywords: Amazonian museums. Social Museology. Decolonization. Cultural Resistance